Transboundary nomadic population movement: a potential for import-export of poliovirus - Samuel Bawa; Mojisola Afolabi; Khalid Abdelrahim; Goni Abba; Adamu Ningi; Salome Yakubu Tafida; Sisay G. Tegegne; Charity Warigon; Terna Nomhwange; Sadiq Abubakar Umar; Aron Aregay; Ahmed Fanti; et al. (BMC, 2018)
Abstract Background Nomadic populations have a considerably higher risk of contracting a number of diseases but, despite the magnitude of the public health risks involved, they are mostly underserved with few health policies or plans to target them. Nomadic population movements are shown to be a niche for the transmission of diseases, including poliomyelitis. The nomadic routes traverse the northern states of Nigeria to other countries in the Lake Chad subregion. As part of the February 2016 polio supplemental immunization activity (SIA) plans in Bauchi state, a review of nomadic routes and populations identified a nomadic population who originated from outside the international borders of Nigeria. This study describes the engagement process for a transboundary nomadic population and the interventions provided to improve population immunity among them while traversing through Nigeria. Methods This was an intervention study which involved a cross-sectional mixed-method (quantitative and qualitative) survey. Information was collected on the nomadic pastoralists entry and exit points, resting points, and health-seeking behavior using key informant interviews and semistructured questionnaire. Transit vaccination teams targeted the groups with oral polio vaccines (OPVs) and other routine antigens along identified routes during the months of February to April 2016. Mobile health teams provided immunization and other child and maternal health survival interventions. Results A total of 2015 children aged under 5 years were vaccinated with OPV, of which 264 (13.1%) were zero-dose during the February 2016 SIAs while, in the March immunization plus days (IPDs), 1864 were immunized of which 211 (11.0%) were zero-dose. A total of 296 children aged under 1 year old were given the first dose of pentavalent vaccine (penta 1), while 119 received the third dose (penta 3), giving a dropout rate of 59.8%. Conclusions Nomadic pastoralists move across international borders and there is a need for transboundary policies among the countries in the Lake Chad region to improve population immunity and disease surveillance through a holistic approach using the One-health concept.